IMPROVING QUALITY OF LIFE AND PREVENTIVE MEASURES FOR HYPOTHYROIDISM - Umida Dzhuramuradovna Ismailova (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Relevance: Despite the well-studied etiology, pathogenesis and simple diagnosis, in some cases the disease remains unrecognized for a long time, which is due to the slow increase in thyroid deficiency and, accordingly, the severity of the clinical picture. Hypothyroidism is one of the most common diseases of the endocrine system. The biological action of thyroid hormones is very diverse: by activating the transcription of numerous genes, they participate in the regulation of basic physiological processes in the body, therefore their deficiency can manifest itself in a wide variety of clinical manifestations and symptoms and imitate diseases of almost all body systems [1]. Among diseases of the endocrine system, hypothyroidism is the second most common after diabetes mellitus. The difficulty of diagnosing hypothyroidism lies in the diversity and non-specificity of symptoms. This is due to the fact that thyroid hormones have an effect on almost all organs and systems. At the same time, the severity of manifestations of thyroid insufficiency can be different and does not always correlate with the severity of laboratory changes. The clinical picture of a patient with hypothyroidism may present multiple symptoms, which makes diagnosis difficult, especially in elderly and multimorbid patients [2Thyroid hormone (Т3) – triiodothyronine plays a critical role in metabolism and organ physiology, and thyroid disease is one of the most common types of metabolic disorders. Hypothyroidism syndrome is perhaps the most common pathology of the endocrine system. Thyroid dysfunction is one of the leading endocrine diseases. Previous data shows that about half of the population with thyroid dysfunction remains undetected. The pattern of thyroid dysfunction appears to depend on the iodine status of the population. The prevalence of thyroid dysfunction may be a parameter to consider when assessing iodine deficiency diseases in a population. European estimates place its prevalence at 5% of the population. However, up to 5% of people may have undiagnosed thyroid hormone deficiency. Deficiency or excess of T3 in humans results in abnormal metabolic rates and adversely affects the physiological functions of many organs such as the heart and liver [3]. Hypothyroidism is a deficiency of thyroid hormones in the body.Based on pathogenesis, hypothyroidism is divided into primary and secondary.